PENGARUH DENSITAS MINYAK BUMI TERHADAP OIL LOSSES PADA PENCAMPURAN MINYAK BUMI DI LAPANGAN ‘X’ SUMATRA SELATAN - Hariyadi Hariyadi; Dedy Kristanto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Field experience shows that, when two or more oils have different densities mixtures and transported throughthe pipeline at the same time, the mixtures will form a new characteristics of oils that different than oilsinitially, then the volume of the oil mixture is delivered from the SP ( Gathering Station), as the transferpoint, the volume will be different on the tank received. Differences between the sending and receiving ofthese so-called oil losses. One factor is the shrinkage volume of oil that caused the process of mixing two ormore of oils which have different characteristics in the pipeline or tank .Laboratory testing use to calculateshrinkage of oil, but the other use the American Petroleum Institute method.In a case study conducted in theoil field 'X' in South Sumatra there are some groups that have different characteristics of petroleum, andfrom laboratory experiments and mathematical calculations showed that the shrinkage in the Group 1 isequal to 0.115% or 2.386 BOPD, shrinkage in the Group 2 is equal to 0131% or 3.931 BOPD. The amountof shrinkage in Group 3 of 0.476% which is equivalent to 6.748 BOPD and for Group 4 seen that shrinkageof this group amounted to 0.189% or 2.082 BOPD and shrinkage for Group 5 amounted to 5% or 38.507BOPD. While the total shrinkage in the network system from upstream to downstream (group 1- 5) isapproximately 0.257%, or approximately 54.37 BPOD